Seven new South American species of Regalana DeLong & Freytag (Cicadellidae: Iassinae: Gyponini) - Domahovski, Alexandre Cruz; Gonçalves, Clayton Corrêa; Takiya, Daniela Maeda; Cavichioli, Rodney Ramiro (Zootaxa, 2014)
Seven new species of the previously monotypic genus Regalana DeLong & Freytag, 1975, described from Panama, are described and illustrated. The new species are described from lowland and montane Amazonian/Andeanrain forests and Cerrado savanna of Brazil, Ecuador, French Guiana, and Peru. They can be distinguished from each other, as well as from the type-species, R. corona DeLong & Freytag, 1975, mainly by features of the aedeagus. A key to the now eight known species of Regalana is provided.